EARLY DETECTION RISK FACTORS OF PREECLAMPSIA: SCOPING REVIEW - Siti Sopiatun; Asri C. Adisasmita (Muhammadiyah International Public Health and Medicine Proceeding, 2024)
Preeclampsia (PE) is a multisystem disorder affecting 2%-5% of pregnancies and remains a leading contributor to maternal and perinatal morbidity and mortality, particularly in cases of early onset. The disorder, commonly emerging around the 20th week of gestation, has a prevalence of approximately 14.1% and is a frequent pregnancy complication. This scoping review aims to examine recent studies on the early detection of pre-eclampsia risk factors. Articles published between 2016 and 2021 were sourced from databases such as PubMed, Google Scholar, Scopus, and Science Direct. Nine studies met the inclusion criteria. These studies explore prediction models for gestational hypertension and preeclampsia, with three focusing on symptoms, signs, laboratory tests, biomarkers, and other associated risk factors. One study highlights family history, obesity, chronic illness, anemia, and lack of ANC visits as contributing factors. Two articles address the management of preeclampsia through initiatives like the PRE-EMPT (Eclampsia Monitoring, Prevention, and Treatment), while others emphasize community-level interventions and healthcare provider education (CLIP). Effective early detection models are essential to reduce preeclampsia incidence and prevent maternal and fetal mortality.